Hyaluronic Acid Fillers and ASIA Syndrome: Case Studies - Owczarczyk-Saczonek A; De Boulle K (Dove Medical Press, 2023)
Agnieszka Owczarczyk-Saczonek,1 Koenraad De Boulle2 1Department of Dermatology, Sexually Transmitted Diseases and Clinical Immunology, Collegium Medicum, University of Warmia and Mazury, Olsztyn, Poland; 2Aalst Dermatology Clinic, Aalst Belgium and University College London, London, UKCorrespondence: Agnieszka Owczarczyk-Saczonek, Email agnieszka.owczarczyk@uwm.edu.plAbstract: A continuous increase in the popularity of esthetic procedures with the use of substances as HA has been observed for many years, which might be contributing to an increase in the number of adverse events. The autoimmune/inflammatory syndrome induced by adjuvants (ASIA) can be provoked by hyaluronic acid (HA), which belongs to substances meeting the criteria of adjuvants. Mechanisms of the innate and acquired immune response are activated, leading to the dysregulation of T and B lymphocytes, inability to recognize one's own antigens, inflammation, damage to one's own tissues, and ultimately to autoimmunity. The objective of this article is to present a case-series study of patients who developed ASIA syndrome following HA injection after delayed inflammatory reaction (DIR) and emphasize the importance of the need for long-term monitoring after such the reaction. Lack of knowledge about ASIA can lead to delayed diagnosis and serious consequences for the patients. People with a history of immunization reactions, severe allergic reactions, individual predisposition to autoimmunity or family predisposition to autoimmunity and previous exposure to adjuvants require special attention and long-term follow-up. This applies primarily to cases of DIR after the using of bioimplants, especially with treatment resistance, as in our reported cases.Keywords: hyaluronic acid, bioimplants, ASIA syndrome, immunogenicity